PERBANDINGAN STANDAR AKUNTANSI ATAS PERTAMBANGAN BATUBARA ANTARA FASB, IFRS DAN PSAK - AGUSTINNE AGUSTINNE (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
Indonesia's coal mining industry is one of the management of natural resources of minerals that affect a very large source of revenue for the State that plays an important role affecting the livelihood of the community. With the rapid development of the coal mining business in Indonesia, then this sector has played an important role as more land mines and increasing monthly production of coal mining in Indonesia. Issue guidelines for the presentation and disclosure of financial statements for Publicly Listed Companies in the field of coal mining industry is in need of a framework that can be used as preparation Universal prevailing global standards. The purpose of this study was to determine how the accounting standard for asset exploration and evaluation of mineral resources of coal that is applied by the FASB, IFRS and GAAP, the accounting standards for the exploration and evaluation of mineral resources of coal are suitable to be applied in Indonesia and the problems encountered in the application of the accounting standards. After doing some research, it can be seen the difference the application of accounting standards for exploration and evaluation assets between FASB, IFRS and GAAP. Accounting standards suitable to be applied in Indonesia to exploration and evaluation assets on mineral resources of coal in Indonesia.